Toyota 2010 : on the way to becoming the world's largest automaker, Toyota hit a rough road - Swersey, Arthur J.; Smith, Andrea Nagy; Forman, Catherine; Elias, Jaan ([London] : SAGE, 2016)
In winter 2010, the Toyota Motor Corporation faced a crisis. Following a number of highly publicized accidents involving Toyota vehicles, the company was forced to recall millions of cars with potentially deadly defects. Customers fled the showrooms and Toyota sales in the U.S. dropped 16% in January 2010. This study explains how the company dealt with these unforeseen issues.
Originally Published in: Swersey, A., Nagy Smith, A., Forman, C., & Elias, J. (2010). Toyota 2010: On the Way to Becoming the World's Largest Automaker, Toyota Hit a Rough Road. 09-040. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Toyota Jidosha Kogyo Kabushiki Kaisha; Quality control -- Case studies; Corporate culture -- Case studies; Crisis management -- Case studies